COVID-19 oriented HRM strategies influence on job and organizational performance through job-related attitudes - Agnieszka Bieńkowska; Anna Koszela; Anna Sałamacha; Katarzyna Tworek (PLoS ONE, 2022)
The COVID-19 crisis forced many changes to occur within organizations, which were necessary to keep the continuance of the organization’s operations. Job performance seems to be an important factor determining such continuance, through its influence on the performance of entire organization. Shaping and keeping job performance in times of COVID-19 pandemic was a challenge for organizations, due to its negative impact on employees, causing their stress or lack of sense of security. There is a growing role of HRM specialists in appropriately shaping HRM strategies that can positively shape job-related attitudes, resulting in enhanced job performance during such difficult times. Therefore, this study aims to explain the role of COVID-19 oriented HRM strategies in shaping job performance through job-related attitudes such as work motivation, job satisfaction, and organizational commitment in a time of crisis occurring in the organization due to the COVID-19 pandemic. The study was conducted among 378 organizations operating in Poland during 2nd wave of COVID-19 pandemic. To verify the hypotheses, descriptive statistics were calculated using IBM SPSS and path analysis was performed using IBM AMOS. The result shows that combined set of "hard" HRM strategies related to the financial aspects and "soft" HRM strategies related to keeping employees’ wellbeing during the crisis gives the best results in shaping job performance through job-related attitudes and consequently strengthening organizational performance. This study contributes to the knowledge concerning the development of COVID-19 oriented HRM strategies, which may also have practical application.